1986
DOI: 10.1002/hon.2900040303
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and DNA‐inhibitory effects of iron chelators on human leukaemic cell lines

Abstract: Cytotoxic and DNA synthesis inhibitory effects of several iron chelators with different physicochemical properties have been tested in four myeloid leukaemic cell lines (U937, K562, ML2 and HL60). The small lipophilic chelators 8-hydroxyquinoline, tropolone and omadine at 2 X 10(-5) M, caused substantial inhibition of labelled leucine and thymidine uptake into cells and also cell death following 4-h incubation. These effects were approximately 10-fold increased when the drugs were pre-incubated with equimolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…The antiproliferative activity of iron chelators was first demonstrated on leukemia in cell cultures and clinical trials [24, 25]. Then, the antiproliferative activity of iron chelators was demonstrated in solid tumors, including pancreatic cancer tumors, and in cell culture in recent studies [15, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…The antiproliferative activity of iron chelators was first demonstrated on leukemia in cell cultures and clinical trials [24, 25]. Then, the antiproliferative activity of iron chelators was demonstrated in solid tumors, including pancreatic cancer tumors, and in cell culture in recent studies [15, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Deferoxamine (DFO), which is produced by Streptomyces pilosus, binds to iron and acts as an iron chelator in cells [Keberle, 1964]. DFO has been shown to exert an anti-proliferative effect on certain cancer cell lines, including hepatoma, leukemia, and neuroblastoma cells [Lederman et al, 1984;Kontoghiorghes et al, 1986;Brodie et al, 1993;Fan et al, 2001]. Also, DFO regulates the expression of many genes such as cytochrome c oxidases and ubiquinone oxidoreductase involving in ATP synthesis [Ye and Connor, 1999].…”
mentioning
confidence: 99%
“…Further experiments with omadine showed that this compound was almost immediately cytotoxic to NB cells, since if the ligand was removed from cells within 3 h, the cells continued to die (Blatt et al 1989). Addition of Fe to omadine did not prevent or enhance the ability of this chelator to inhibit NB growth (Blatt et al 1989), which is in contrast with other work with leukemic cells, which showed that the addition of Fe to this ligand enhanced its cytotoxicity (Kontoghiorghes et al 1986a(Kontoghiorghes et al , 1986b. This latter investigation suggested that the ability of omadine to inhibit proliferation was probably not by the same mechanism as that found for DFO.…”
Section: (A) Effect Of Dfo On Human Tumor Growthmentioning
confidence: 71%